PENERAPAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE BERBANTUAN KARTU GAMBAR BERSERI TERHADAP KETERAMPILAN MEMBACA PESERTA DIDIK KELAS II SD MUHAMMADIYAH 09 MEDAN - Ardina Irani Pasaribu; Mustika Roudhoh; Dyra Amanda; Melyani Sari Sitepu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the Inside Outside Circle (IOC) learning model assisted by serial picture cards on students’ reading skills. The low level of students’ reading skills is caused by the lack of variation in learning models and the limited use of interesting instructional media. This study employed a quantitative approach using a quasi-experimental design. The research subjects were elementary school students who were divided into an experimental class and a control class. The experimental class was taught using the Inside Outside Circle learning model assisted by serial picture cards, while the control class used conventional learning methods. Data were collected through reading skill tests, observation, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing with a t-test. The results showed that there was a significant difference in reading skills between students who were taught using the Inside Outside Circle learning model assisted by serial picture cards and those who were taught using conventional methods. Therefore, it can be concluded that the implementation of the Inside Outside Circle learning model assisted by serial picture cards has a positive effect on improving students’ reading skills. This learning model can be used as an effective alternative to enhance reading skills in elementary schools.